Analisis Pengaruh Iklan, Kepercayaan Merek, dan Citra Merek terhadap Minat Beli Konsumen - Arista, E Desi; Astuti, Sri Rahayu Tri (Jurnal Ilmu Ekonomi ASET, 2011)
Globalization era makes information and technologies increase very fastand can be known quickly. One of information technology is the Interconnected Network,or more popular as the Internet. Therefore, to satisfy consumers PT. Telkom issued aproduct called Speedy. Many factors influence customers before purchasing a productconsumers. The purpose of this study is to determine the influence of advertising, brandtrust and brand image to the buying interest. Brand trust is the highest independentvariable that influences the dependent variable (buying interest) then advertising andlastly the brand image.Keywords: advertising, brand trust, brand image, buying interest.